HuR Affects Proliferation and Apoptosis of Chronic Lymphocytic Leukemia Cells via NF-κB Pathway. (28th August 2020) - Xiao, Kai; Yang, Lin; Gao, Xinfeng; An, Ying; Xie, Wei; Jingquan, Guo
Abstract : Objective . To investigate the effects of HuR protein on the treatment of chronic lymphocytic leukemia (CLL). Methods . LCL lymphoblast cells and B lymphocytes were subjected to HuR overexpression (OV) or interference (IV). Western blot was used to observe the protein expression of human tumor necrosis factor-associated factor 1 (TRAF1), human inhibitor of nuclear factor kappa-B kinase α (IKK- α ), NF- κ B-inducing kinase (NIK), and p52. Flow cytometry was performed to evaluate apoptosis, and the mRNA expression of TRAF1 was examined by quantitative reverse transcription polymerase chain reaction. Immunofluorescence was carried out to visualize the expression of HuR, and the relationship between HuR and TRAF1 was observed by pull-down test. Cell sensitivity to chlorambucil (CLB) and fludarabine (Flu) was assessed by Cell Counting Kit-8. Results . The expression of HuR and TRAF1 in LCLs was significantly increased compared to that in B lymphocytes. Compared with the control, HuR OV significantly increased the expression of TRAF1 (P < 0.05 ), whereas it was significantly decreased in the IV group (P < 0.05 ). HuR can bind to TRAF1 directly, and the binding rate is positively correlated with HuR expression. After inhibiting HuR, the expression of TRAF1, IKK- α, NIK, p52, pro-Caspase 3, and PARP was significantly upregulated in LCLs and B lymphocytes (P < 0.05 ), while Caspase 3 was downregulated (P < 0.05 ). Compared with the control, the proliferation of LCLs and B lymphocytes treated by CLB and Flu decreased significantly after HuR blockade (P < 0.05 ). Conclusion . HuR may be a key protein regulating CLL resistance. After inhibiting HuR, inflammatory response and apoptosis were significantly increased, and the cell sensitivity to CLB and Flu increased, suggesting that inhibiting HuR activity may be a potential strategy to solve the problem of drug resistance in CLL cells.